CASE STUDY OF FISTULOGRAPHY EXAMINATION PROCEDURES IN CASES PERIANAL FISTULA IN THE RADIOLOGY INSTALLATION RSUD DR. LOEKMONO HADI KUDUS - Nur Annisa; Ari Anggraeni (Journal of Indonesian Anesthesiology Nursing, 2024)
ABSTRACT Fistulography radiographic examination in cases of perianal fistula in the Radiology Installation using conventional aircraft and Anteroposterior (AP), Right Posterior Oblique (RPO) projections. According to Long et al., (2014) the tools used by fluoroscopy use AP, AP axial, AP oblique and lateral projections. According to Hulmansyah (2024), projection (AP), Lateral and Oblique. The aim of this research is to find out the fistulography examination procedure in cases of perianal fistula, find out the reasons for inserting contrast media from different organs, namely the scrotum and anus and find out the reasons for using protruding ( AP ), and (RPO). This type of research is qualitative with a case study approach. The research was conducted at the Radiology Installation October – July 2024. The data collection method was carried out by observation, documentation and interviews with 3 radiographers and 1 radiology specialist. The implementation period will be from September to June 2024 with one patient. Data analysis was obtained from data collection in the hospital, then the data was presented in a scientific paper and conclusions were drawn. The results of the research were fistulography examinations in perianal fistula cases in the Radiology Installation carried out using AP and RPO projections and the introduction of contrast media from different organs, namely the scrotum and anus. The reason for using AP and RPO projections in fistulography examinations is to display the fistula from the front and side views. The reason for inserting contrast media into two different organs is to show whether the channels are connected. This study shows that this approach is effective enough to support the diagnosis and evaluation of perianal fistula structures, providing optimal procedural guidance in clinical radiology practice in regional hospitals